2019
DOI: 10.1002/lary.27816
|View full text |Cite
|
Sign up to set email alerts
|

Sonolocation during submandibular sialolithotomy

Abstract: Objectives/Hypothesis Ultrasound is a proven tool for diagnostic and therapeutic purposes for treatment of salivary gland pathology. It is also useful for localization of calculi during submandibular gland transoral sialolithotomy when calculi cannot easily be palpated. Our objective was to determine the efficacy of sialolith localization using ultrasound during submandibular gland sialolithotomy. Study Design Retrospective case series. Methods A study performed utilizing data compiled from 2009 through 2016 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Numerous studies have documented different ways to avoid damage to the gland during surgery by utilizing imaging techniques, such as ultrasound and cone beam computed tomography (CT) pre-operatively and intra-operatively. 29,30 The use of CT to identify stones appears to be more accurate than ultrasound, but not always available. One study specifically reported on the use of ultrasound-guided needle injection of methylene blue prior to open parotid sialolithotomy in order to better localize the stone intra-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented different ways to avoid damage to the gland during surgery by utilizing imaging techniques, such as ultrasound and cone beam computed tomography (CT) pre-operatively and intra-operatively. 29,30 The use of CT to identify stones appears to be more accurate than ultrasound, but not always available. One study specifically reported on the use of ultrasound-guided needle injection of methylene blue prior to open parotid sialolithotomy in order to better localize the stone intra-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Submandibular stones are thought to form around a nidus of mucous, whereas parotid stones are thought to form most often around a nidus of inflammatory cells or a foreign body. 4 Another theory has proposed that an unknown metabolic phenomenon can increase the salivary bicarbonate content, which alters calcium phosphate solubility and leads to precipitation of calcium and phosphate ions. A retrograde theory for sialolithiasis has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which DD is obviously difficult, ultrasound-guided diagnostic techniques [41,103] and the simultaneous application of US and sialendoscopy added diagnostic value, the latter by providing a singular, real-time, three-dimensional intra-and extraductal overview [103]. Besides this, US provides diagnostic information in the preparation [103,137], as support in the treatment [103,[138][139][140][141][142][143][144][145] and in the (post-therapeutic) follow-up [69,79,146] in sialolithiasis.…”
Section: Obstructive Sialadenitis Caused By Sialolithiasismentioning
confidence: 99%